2021
DOI: 10.3390/jcm10214925
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in COVID-19 Compared to Non-COVID-19 Cohorts: A Systematic Review with Meta-Analysis

Abstract: Background: A high incidence of venous thromboembolism (VTE) is reported in hospitalized COVID-19 patients, in particular in patients admitted to the intensive care unit (ICU). In patients with respiratory tract infections, including influenza A (H1N1), many studies have demonstrated an increased incidence of thromboses, but evidence is lacking regarding the risk difference (RD) of the occurrence of VTE between COVID-19 and non-COVID-19 patients. Methods: In this systematic review with meta-analysis, we evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 43 publications
(94 reference statements)
1
26
0
1
Order By: Relevance
“…This is in contrast to our STEMI patients, who can be treated by CRP apheresis via peripheral access [ 12 14 ]. This clotting is probably due to the known hypercoagulability in COVID-19 [ 24 ], and may also be caused by hemodynamic centralization in these severely ill patients. Thus, we now use Shaldon catheters for CRP apheresis in our COVID patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to our STEMI patients, who can be treated by CRP apheresis via peripheral access [ 12 14 ]. This clotting is probably due to the known hypercoagulability in COVID-19 [ 24 ], and may also be caused by hemodynamic centralization in these severely ill patients. Thus, we now use Shaldon catheters for CRP apheresis in our COVID patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis revealed an estimated venous thromboembolism (VTE) rate of 25%, with higher incidence in severe cases, such as those who are on mechanical ventilation [ 24 ]. The risk for VTE in COVID-19 compared to non-COVID-19 (other respiratory tract infections including H1N1) patients was 6% higher in general and the risk increased further to 16% in ICU patients when these two categories were compared [ 25 ]. Furthermore, the number of ischemic strokes' reports during COVID-19 infection is increasing [ 26 , 27 ].…”
Section: Pathophysiology Of Covid-19-associated Coagulopathymentioning
confidence: 99%
“…When comparing COVID-19 patients to non-COVID-19 patients, an elevated risk of venous thromboembolism has been shown. It has been reported that critically ill COVID-19 patients have a 16% higher risk of developing venous thromboembolism when compared to non-COVID-19 patients [6]. There are several possible explanations for this.…”
Section: Introductionmentioning
confidence: 98%